1996
DOI: 10.1046/j.1365-2133.1996.d01-1093.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and D expression in squamous cell carcinoma

Abstract: To elucidate involvement of proteinases in malignancy of keratinocytes, expression of cathepsin B, a cysteine proteinase, and cathepsin D, an aspartic proteinase, was ascertained in formalin-fixed paraffin-embedded specimens of normal skin, squamous cell carcinoma (SCC). Bowen's disease, seborrhoeic keratosis and basal cell carcinoma (BCC). Presence of procathepsin B and an intermediate form of cathepsin D was confirmed by Western blotting and enzyme activity analysis. Cathepsin B stained more intensely in SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This lysosomal cysteine protease is overexpressed in cancer cells, such as gastric or colon cancers 24, 25. Squamous cell carcinoma cells (SCC-7) was also confirmed that it express high levels of cathepsin B 26, 27. Because overexpressed MMPs and cathepsin B play important biological functions in tumor, many imaging probes targeting these proteases have been developed for cancer diagnosis 28, 29.…”
Section: Introductionmentioning
confidence: 94%
“…This lysosomal cysteine protease is overexpressed in cancer cells, such as gastric or colon cancers 24, 25. Squamous cell carcinoma cells (SCC-7) was also confirmed that it express high levels of cathepsin B 26, 27. Because overexpressed MMPs and cathepsin B play important biological functions in tumor, many imaging probes targeting these proteases have been developed for cancer diagnosis 28, 29.…”
Section: Introductionmentioning
confidence: 94%
“…Kawada et al [21] noted that half of SCC cases showed enhanced cathepsin D expression, but Bowen's disease, SK, or BCC did not show any staining for cathepsin D. They concluded that upward production of cathepsin D might be associated with malignancy of keratinocytes. It has also been suggested that the catalytic activity of secreted cathepsin D may be implicated in releasing growth factors, such as fibroblast growth factor-2, from the ECM [22].…”
Section: Discussionmentioning
confidence: 95%
“…However, we emphasize that our observations should be evaluated in a larger series of prostate samples before a definitive conclusion can be reached. Previously, Kawada et al (1996) observed diffuse immunostaining for proenzyme and granular staining for mature CB in squamous cell cancer and suggested that there may be some differences in subcellular localization of these two forms of CB. Distribution of mature CB has been reported in several malignant tumors of solid organs (see Campo et al, 1994;Sloane et al, 1994a,b;Elliott and Sloane, 1996).…”
Section: Discussionmentioning
confidence: 99%